PSYCHOSOCIAL DEVELOPMENT OF ANNA FITZGERALD IN MY SISTER’S KEEPER NOVEL BY JODI PICOULT - Ayu Meriska; Surya Sili; Erna Wati (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2018)
Commonly, parents decide to have children to complete their live as part of their family. Then, how about the parents who have another reason with the presence of their children? It can make the children to have different thinking with other and it can make the children wonder about their true status or identity in family. It is because parents and their children do not have the similar purpose in their family. This situation happened in My Sister’s Keeper novel. The researcher choose to analyse Anna Fitzgerald in the novel because the life of family in My Sister’s Keeper novel was not like other family in general. The researcher analysed Anna Fitzgerald’s character through two theories to find out her identity. Erikson’s psychosocial development in the fifth stage was used to analyse of how Anna Fitzgerald got through the development as thirteen years old children in defining her own identity, successfully or not. It was because this stage discusses about the process of finding the true identity. Meanwhile, the researcher used Bowlby’s attachment theory to analyse of Anna’s relationship with her mother. Also, in this theory, the researcher only used one characteristic (proximity maintenance) to know about factor that influence of Anna’s position in Erikson’s fifth stage. This research was aimed to find out about the identity in fifth stage of psychosocial development of a child who lived uncommon situation and the factor that influenced her identity. The result of this research showed that Anna psychosocially experienced role confusion because she failed to know about her true identity. This situation influenced Anna’s relationship with her mother. As a result, she did not have fidelity as her basic virtue. Anna did not get the sense of safety and comfort from her relationship with Sara, as mother-daughter relationship.  Key words: Psychosocial Development, Attachment Theory